Cybersecurity and Major Cyber Threats of Smart Meters: A Systematic Mapping Review - Jones Márcio Nambundo; Otávio de Souza Martins Gomes; Adler Diniz de Souza; Raphael Carlos Santos Machado (Energies)
Smart meters are a vital part of the smart grid, enabling energy management, real-time control, and data collection. Despite advances in technology, there is still a lack of content and limited understanding of the specific cybersecurity threats facing these devices, as well as the effectiveness of existing mitigation strategies. This study analyzed 41 articles sourced from three academic databases (Scopus, Web of Science, and IEEE Xplore). A cutting-edge study was conducted, including a comprehensive review of relevant literature on smart meters, cybersecurity vulnerabilities, and mitigation strategies. Elements were selected based on pre-assessment and classification processes, and the data were extracted and combined to provide detailed insights into the new devices. The study identified several significant cybersecurity risks for smart meters, including data breaches, unauthorized access, data manipulation, denial-of-service (DoS) attacks, and malware introduction. The study also highlighted the vulnerabilities exploited by these threats, such as undocumented communications, weak authentication, and outdated software. Recommended mitigation strategies include strengthening access and authentication mechanisms, securing communication systems, regular software updates, code management, anomaly detection, and access control. The findings indicate that although there are good strategies and methods to mitigate these cyber threats, significant research gaps remain. These gaps include design requirements, software and firmware updates, physical security, the use of big data to detect vulnerabilities, user data privacy, and inconsistencies in machine learning algorithms. Future research should focus on these aspects to improve the stability and reliability of smart meters.